"Not a cookie cutter situation": how neurodivergent students experience group work in their STEM courses - Sophia Salvatore; Claudia White; Stephen Podowitz-Thomas (SpringerOpen, 2024)
Abstract Background Although group work is increasingly used in STEM courses and may lead to improved academic outcomes, there is evidence that some implementations of group work may lead to unintended barriers for certain students' learning. Despite the growing number of neurodivergent undergraduate students, there is limited research on neurodivergent students' experiences with group work in STEM courses. To address this knowledge gap, the current research investigated the experiences of 22 neurodivergent undergraduate students with group work in STEM courses at a range of institution types and in a variety of STEM disciplines. Participants shared experiences with in-class and out-of-class group work assignments for lecture and laboratory courses. Results Through inductive thematic coding of semi-structured interview transcripts, we identified seven themes impacting participants' experiences. Three themes were individual level: personal characteristics that participants associated with their neurodivergence; strategies for academic success (with subthemes of organization/time management, adaptive communication, and self-advocacy); and beliefs on group work's value. Four themes were group level/classroom level: group dynamics; role in group (including leadership roles); the competitive culture within STEM; and recommendations for instructors. Through a social-relational perspective on disability, we proposed a model showcasing how group and classroom factors serve as supports or barriers to neurodivergent students' full participation in group work, as well as to their sense of belonging. Using the seven themes we articulated, we outlined a set of practices for designing group work assignments. In addition, we propose how pairing inclusive assignment design with instructor reflection and articulating anti-ableist values can support neurodivergent student belonging by disrupting discourses of normalcy in STEM. Conclusions As one of the first studies exploring the impact that group work in STEM courses has on neurodivergent undergraduates, this work may inform reimaginations of group work practices to better address the needs of neurodivergent STEM students and support a more inclusive culture in STEM classrooms. In addition, our conceptual model may serve as the basis for future research regarding interactions between individual-level and group-level factors associated with neurodivergent students' learning through group work and other active learning practices.